Structural reorganization in a hydrogen-bonded organic framework. (12th September 2018) - Castells-Gil, Javier; Padial, Natalia M.; Martí-Gastaldo, Carlos
Abstract : Self-recognition of 3, 3′, 5, 5′-azobenzenetetracarboxylic acid yields a grid-like anionic hydrogen-bonded framework capable of undergoing structural reorganization by recrystallization in the presence of guanidinium cations. Abstract : Self-recognition of 3, 3′, 5, 5′-azobenzenetetracarboxylic acid drives the formation of a grid-like anionic hydrogen-bonded framework with channels occupied by organic cations. This supramolecular solid is capable of reorganizing its connectivity in the presence of specific guests into a different crystalline architecture by sequential dissolution and recrystallization.